VLSI-SoC : opportunities and challenges beyond the internet of things : 25th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2017, Abu Dhabi, United Arab Emirates, October 23-25, 2017, Revised and Extended Selected Papers /: opportunities and challenges beyond the internet of things : 25th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2017, Abu Dhabi, United Arab Emirates, October 23-25, 2017, Revised and Extended Selected Papers. (2019) - Unknown
No abstract available